(untitled) (Libyan Journal of Ecological & Environmental Sciences and Technology, 2022)
Phytoremediation of drilling waste, and contaminated soils were tested using a commercial mixture of poaceae, (Festuca arundinacea, Poa pratensis and Lolium perenne). The experiment evaluated the ability of grass to survive, and the degradation of petroleum hydrocarbons in contaminated soils. The mixture of grass was planted in soil comprising different ratios of soil: waste (0, 25, 50 and 75% of water-based drilling waste) to examine the effect of a range of total petroleum TPHs concentrations. Biomass measurements including shoot and root biomass, grass height, and leaf chlorophyll content, were made, in addition to determining the occurrence of any reduction in leachability of total petroleum hydrocarbons contamination. Finally, the role of microorganisms and enzymes in the dissipation of petroleum hydrocarbons was observed. This research found that the mixture is useful for the phytoremediation of soils contaminated by drilling waste. The grasses also are shown to have the potential to remediate soils contaminated by petroleum hydrocarbons when the contamination level is below 50% (0.25 wt. % or 2488 mgKg-1 TOC) where the petroleum hydrocarbon concentration in each successful treatment (25% and 50%) were removed by the efficiency of gross petroleum hydrocarbon degradation of 74 %, and 59.6 %, respectively. The findings also prove that the use of grasses mixture enhances the microbial enumeration in the root zone which is expected in helping the uptake and/or degradation of petroleum hydrocarbons for up to 52 days. The mixture of grasses offers an environmentally friendly, cost-effective, waste management option for some sites despite the need for long time. These findings indicate that more studies are much needed in the field of phytoremediation.